Rapid pseudo five-component synthesis of intensively blue luminescent 2,5-di(hetero)arylfurans via a Sonogashira–Glaser cyclization sequence - Klukas, Fabian; Grunwald, Alexander; Menschel, Franziska; Müller, Thomas J. J. (Beilstein Journal of Organic Chemistry, 2014)
2,5-Di(hetero)arylfurans are readily accessible in a pseudo five-component reaction via a Sonogashira–Glaser coupling sequence followed by a superbase-mediated (KOH/DMSO) cyclization in a consecutive one-pot fashion. Besides the straightforward synthesis of natural products and biologically active molecules all representatives are particularly interesting due to their bright blue luminescence with remarkably high quantum yields. The electronic structure of the title compounds is additionally studied with DFT computations.
Keywords: C–C coupling; copper; DFT; fluorescence; furans; mircowave-assisted synthesis; multicomponent reactions; palladium